Music therapy in alzheimer's disease and its cognitive, psychological, and behavioral effects: A systematic review (Horizontes de Enfermería, 2025)
Alzheimer's disease is a chronic neurodegenerative condition that affects memory, thinking and behavior, leading to a progressive decline in cognitive and behavioral functions. Non-pharmacological therapies are presented as effective options for optimizing the quality of life of patients with Alzheimer's. The objective was to define the main benefits of music therapy in patients with Alzheimer's, in the cognitive, psychological, and behavioral areas. To answer the research question: What are the effects of music therapy on the cognitive, psychological, and behavioral functions of patients with Alzheimer’s? A systematic review of articles published between 2015 and 2024 was conducted. The databases used were PubMed, Science Direct, Elsevier, and the Virtual Health Library. The search terms included "music therapy," "Alzheimer's," "cognitive," "psychological," and "behavioral." Twenty-nine studies were selected that met the inclusion criteria. The review found that music therapy significantly improves memory, attention, and global cognition. In addition, a significant reduction in anxiety and depression levels was observed, contributing to the emotional and behavioral stabilization of patients. Out of the 29 studies reviewed, most indicated that benefits are most evident when patients are actively involved in music creation. Music therapy is presented as an effective non-pharmacological strategy for optimizing the quality of life of Alzheimer's patients by promoting cognitive function.
Keywords: Music Therapy; Alzheimer's; Cognition; Behavior; Nursing